Sensitivity of foraminiferal-based indices to evaluate the ecological quality status of marine coastal benthic systems: A case study of the Gulf of Manfredonia (southern Adriatic Sea). (February 2021) - Fossile, Eleonora; Sabbatini, Anna; Spagnoli, Federico; Caridi, Francesca; Dell'Anno, Antonio; De Marco, Rocco; Dinelli, Enrico; Droghini, Elisa; Tramontana, Mario; Negri, Alessandra
Abstract: This paper aims to compare two foraminiferal based biotic indices generally used to evaluate the ecological quality status (EcoQS): the Foram-AMBI and the Foram Stress Index (FSI). For this purpose, we report the distribution and diversity of living foraminiferal assemblages and the environmental variables from a bathymetric transect in the Southern Adriatic Sea. The two indices agree well with the detected organic enrichment but indicate conflicting EcoQS as the Foram-AMBI detects good environmental conditions, whereas the FSI describes a poor-moderate quality. Many species not assigned (including soft-shelled foraminifera) are to blame for the different results. Also, both foraminiferal-based indices neglect the heavy metal increase encountered in the deepest stations. These findings suggest the need for a more in-depth analysis to improve the ecological status evaluation of marine benthic systems, including other descriptors as chemical pollutants in combination with biotic indices sensitive to organic matter enrichment. Graphical abstract: Unlabelled Image Highlights: Living benthic foraminifera are used to assess the Ecological Quality Status. Two biotic indices are compared: the Foram-AMBI and the Foram Stress Index. The indices are well correlated with the organic enrichment. The tested biotic indices require an improvement. Ecological status evaluation needs the combination of biotic and abiotic variables.